2019
DOI: 10.1029/2018jd029756
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Space Traffic Effects in SBUV Polar Mesospheric Cloud Data

Abstract: Water‐rich rocket exhaust plumes, in particular those emitted by the National Aeronautics and Space Administration Space Shuttle, have been suggested to make a significant contribution to long‐term trends in polar mesospheric cloud (PMC) ice water content. We investigate this claim using the combined Solar Backscatter Ultraviolet (SBUV) PMC data record from eight separate instruments, which includes 60 Shuttle launches during PMC seasons between 1985 and 2011. No statistically significant postlaunch signal in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Where For this comparison, we used the MIMAS run A, in which the simulations are performed with increasing concentrations of CO2 and CH4. For the comparison, we applied the same calculation method to our model data as Hervig et al (2019) did on satellite observations, namely, we used a threshold of 50 g/km 3 for integrated water content because the PMC detection threshold for SBUV is 50 g/km 3 (DeLand and Thomas, 2015Thomas, , 2019.…”
Section: Solar Cycle Response In Ice Water Content (Iwc)mentioning
confidence: 99%
“…Where For this comparison, we used the MIMAS run A, in which the simulations are performed with increasing concentrations of CO2 and CH4. For the comparison, we applied the same calculation method to our model data as Hervig et al (2019) did on satellite observations, namely, we used a threshold of 50 g/km 3 for integrated water content because the PMC detection threshold for SBUV is 50 g/km 3 (DeLand and Thomas, 2015Thomas, , 2019.…”
Section: Solar Cycle Response In Ice Water Content (Iwc)mentioning
confidence: 99%
“…The variation in Figure 5 is extreme, with the daily ice mass between 0 t and 2 t. Such variability at a fixed LT motivates us to consider another source of cloud formation, so we consider here the advection of space traffic exhaust. A typical vehicle releases 100–600 tons of exhaust during a single launch (Stevens et al., 2012; DeLand & Thomas, 2019a), which is far more than shown in Figure 5 for any given day. By way of comparison with Figure 5, the response in mesospheric cloud ice mass from a space shuttle main exhaust plume in the Arctic can be 262 t/day (Stevens et al., 2005a).…”
Section: Mid‐latitude Mesospheric Cloud Frequencies: 2007–2021mentioning
confidence: 99%
“…These bursts were detected primarily by an increase in PMC frequency, although the cloud brightness can also measurably increase. DeLand and Thomas (2019a) recently studied the impact of all space traffic on relative changes to PMC up to 10 days after launches and found only a limited effect for the latitude band 65°–75°N. However, they emphasized that the small number of cloud detections at more equatorward latitudes (<65°N) prevented them from evaluating the potential link to space traffic there.…”
Section: Introductionmentioning
confidence: 99%
“…Case studies have shown that one burst of these space shuttle‐generated PMCs can account for roughly 10%–20% of the total ice mass observed in one season of observations over the Arctic or the Antarctic (Stevens, Englert et al., 2005a; Stevens, Meier et al., 2005b). These bursts were primarily distinguished by an increase in PMC frequency, rather than brightness (DeLand & Thomas, 2019). However, neither the total contribution of space shuttle launches to the observed numbers of PMC nor the cumulative contribution of space traffic worldwide to the historical cloud record has yet been quantified.…”
Section: Introductionmentioning
confidence: 99%
“…. These bursts were primarily distinguished by an increase in PMC frequency, rather than brightness (DeLand & Thomas, 2019). However, neither the total contribution of space shuttle launches to the observed numbers of PMC nor the cumulative contribution of space traffic worldwide to the historical cloud record has yet been quantified.…”
mentioning
confidence: 99%